Docosahexaenoic Acid Consumption Impedes Early Interferon- and Chemokine-Related Gene Expression While Suppressing Silica-Triggered Flaring of Murine Lupus - Benninghoff, Abby D.; Bates, Melissa A.; Chauhan, Preeti S.; Wierenga, Kathryn A.; Gilley, Kristen N.; Holian, Andrij; Harkema, Jack R.; Pestka, James J. (Frontiers in Immunology, 2019)
Exposure of lupus-prone female NZBWF1 mice to respirable crystalline silica (cSiO2), a known human autoimmune trigger, initiates loss of tolerance, rapid progression of autoimmunity, and early onset of glomerulonephritis. We have previously demonstrated that dietary supplementation with the ω-3 polyunsaturated fatty acid docosahexaenoic acid (DHA) suppresses autoimmune pathogenesis and nephritis in this unique model of lupus flaring. In this report, we utilized tissues from prior studies to test the hypothesis that DHA consumption interferes with upregulation of critical genes associated with cSiO2-triggered murine lupus. A NanoString nCounter platform targeting 770 immune-related genes was used to assess the effects cSiO2 on mRNA signatures over time in female NZBWF1 mice consuming control (CON) diets compared to mice fed diets containing DHA at an amount calorically equivalent to human consumption of 2 g per day (DHA low) or 5 g per day (DHA high). Experimental groups of mice were sacrificed: 1) 1 d after a single intranasal instillation of 1 mg cSiO2 or vehicle, 2) 1 d after four weekly single instillations of vehicle or 1 mg cSiO2, and 3) 1, 5, 9, and 13 weeks after four weekly single instillations of vehicle or 1 mg cSiO2. Genes associated with inflammation as well as innate and adaptive immunity were markedly upregulated in lungs of CON-fed mice 1 d after four weekly cSiO2 doses but were significantly suppressed in mice fed DHA high diets. Importantly, mRNA signatures in lungs of cSiO2-treated CON-fed mice over 13 weeks reflected progressive amplification of interferon (IFN)- and chemokine-related gene pathways. While these responses in the DHA low group were suppressed primarily at week 5, significant downregulation was observed at weeks 1, 5, 9, and 13 in mice fed the DHA high diet. At week 13, cSiO2 treatment of CON-fed mice affected 214 genes in kidney tissue associated with inflammation, innate/adaptive immunity, IFN, chemokines, and antigen processing, mostly by upregulation; however, feeding DHA dose-dependently suppressed these responses. Taken together, dietary DHA intake in lupus-prone mice impeded cSiO2-triggered mRNA signatures known to be involved in ectopic lymphoid tissue neogenesis, systemic autoimmunity, and glomerulonephritis.